Economic Feasibility Analysis, Value Added and Marketing of Semi Refined Carrageenan (SRC) Seaweed Processing Industry - Zakirah Raihani Ya'la (CV. Green Publisher Indonesia, 2022)
Dried seaweed produced by the community in three districts (Morowali, Parigi, and Bangkep) is the final product at the level of seaweed cultivators. They do not yet know about processing seaweed into SRC or gelatin. The research was conducted in Central Sulawesi Province by taking data on the 3 largest seaweed producing districts, namely Banggai Islands Regency, Morowali Regency and Parimo Regency. The main objective of this research is to formulate a strategic plan for the management of seaweed agribusiness through SRC agroindustry and to make it community-based in Central Sulawesi Province. The specific objectives include: Estimating land potential and seaweed production in Bangkep, Morowali, and Parimo Districts, Analyzing the land suitability of locations that are centers of seaweed cultivation in Bangkep, Morowali, and Parimo Districts, Analyzing the economic feasibility of SRC agro-industry and To be medium-scale, to develop a strategy for managing seaweed agribusiness through SRC agro-industry and agar in Central Sulawesi Province, and to empower communities through mentoring in SRC processing training and for the community, especially seaweed cultivators in Bangkep Regency, Morowali Regency and Parimo Regency. The need for primary data on water quality, potential and seaweed production is carried out by survey method by taking samples directly in the field by purposive sampling, namely sampling with certain considerations, sampling only at the cultivation location and simple random sampling, namely taking sample members. from the population randomly without regard to strata and is considered homogeneous in the population. The business feasibility analysis data, seaweed processing technology, and socio-economic data were carried out by direct interviews with structured questionnaires.